A new neotropical genus of the family Cunaxidae (Acari : Prostigmata : Bdelloidea) - Den Heyer, Jacob; Martins Gomes de Castro, Tatiane Marie [UNESP] (Magnolia Press, 2008)
A new Neotropical genus and its species, Allocunaxa heveae gen. et sp. nov., is described and figured. The generic features are provided. The subfamily Cunaxinae is discussed and a key to it is provided.
Keywords: Bdelloidea; Neotropical; Cunaxinae; Taxonomy; identification key